Nonsingular Terminal Sliding Mode Control of the Yarn Winding Process Based on a Finite-Time Extended State Observer - Jieshi Yang; Yinghao Ye; Yun Cheng; Liang Hua (IEEE Access)
Tension control in yarn winding is crucial for maintaining product quality and process continuity in the textile industry, particularly in the presence of varying rotational speeds, winding radii, and external disturbances. To address this issue, this paper proposes a yarn tension sliding mode control method based on a finite-time extended state observer for rapid and accurate tension regulation. Firstly, considering the dynamic characteristics of the tension control system, both internal and external disturbances are expanded into a total disturbance state, and a finite-time extended state observer is established to accurately estimate the system state and total disturbance. Secondly, based on the estimated state, a nonsingular terminal sliding mode control scheme is designed, with an appropriate exponential convergence law chosen to ensure that the system reaches the sliding surface within finite time. The finite-time stability of the estimation error and system tracking error is analyzed using the Lyapunov method. Finally, the simulation results demonstrate that the proposed control scheme effectively achieves finite-time stability of both estimation and tracking errors, and exhibits favorable dynamic characteristics.